ASUHAN KEPERAWATAN PADA AN. S DENGAN SKABIES DI WILAYAH SASAK RAYA KELURAHAN LIMO KOTA DEPOK - Shevia Adinda Nuraini (2023)
Background: Scabies is a disease that can cause discomfort to sufferers due to the clinical manifestations it causes. In general, scabies is not life-threatening however, this disease can be chronic and severe and can cause serious and dangerous complications. So that proper therapy and prevention are needed to control scabies. This study aims to determine the causal factors and how to treat scabies with nursing care in order to reduce the incidence of scabies in children. Methods: this study uses a case study method in nursing care at An. S with scabies in Sasak Raya, Limo Village, Depok City. From 01 March 2023 to 03 March 2023. Data collection was obtained through interviews, observations, physical examinations and documentation. Results: nursing diagnoses that emerged were self-care deficit related to the inability of the family to modify the environment, ineffective family health management related to the inability of the family to recognize the problem, impaired skin integrity related to lack of exposure to information about efforts to maintain/protect tissue integrity. Implementation of nursing actions in accordance with priority issues and outcomes of each diagnosis for 3x24 hours. Impaired skin integrity problems, knowledge deficits and self-care deficits can be resolved. Conclusion: the implementation given by the client is appropriate, based on nursing care. So that the diagnosis is resolved.